International Criminal Law with Asian Characteristics - Chesterman, Simon (Columbia Journal of Asian Law, 2014)
The history of international criminal law typically effaces Asian experience of the topic. This is partly because incidents such as the Tokyo Trial disclose racial and colonial biases that are now seen as embarrassing. Yet failing to engage with Asian experience also impoverishes our understanding of the possibilities and limitations of international criminal law. In particular, pragmatic adaptation of “universal” principles in various Asian jurisdictions offers a helpful lens through which to view the inherent tension between legitimacy and effectiveness in international criminal trials: the desire for legitimacy that goes beyond a state whose leaders may have engaged in unspeakable acts; the need for effectiveness at the local level if any resolution of a conflict is to be enduring. A more nuanced understanding may also help explain an apparent paradox: despite having a long tradition of restrictions on the conduct of hostilities, Asian states today are twice as unlikely to have accepted the jurisdiction of the International Criminal Court when compared with any other region.